2016
DOI: 10.7717/peerj.2758
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of antigen-specific T helper 1 immunity by Neolitsea hiiranensis and its derived terpenoids

Abstract: BackgroundT cells play a pivotal role in the adaptive immunity that participates in a wide range of immune responses through a complicated cytokine network. Imbalance of T-cell responses is involved in several immune disorders. Neolitsea species, one of the biggest genera in the family Lauraceae, have been employed widely as folk medicines for a long time in Asia. Previous phytochemical investigations revealed the abundance of terpenes in the leaves of N. hiiranensis, an endemic Neolitsea in Taiwan, and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, a comparative study of immunomodulatory properties of different Neolitsea species on immunocompetent cells such as T helper cells has not been demonstrated to date. Our previous reported study found that the leaf extracts of N. hiiranensis significantly inhibited IL-12, IFN- γ , and IL-2 cytokine productions as well as the serum levels of OVA-primed antigen-specific IgM and IgG 2a in vivo [ 27 ]. In the present study, we evaluated the immunomodulatory properties of ten Taiwanese Neolitsea plants on T helper cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a comparative study of immunomodulatory properties of different Neolitsea species on immunocompetent cells such as T helper cells has not been demonstrated to date. Our previous reported study found that the leaf extracts of N. hiiranensis significantly inhibited IL-12, IFN- γ , and IL-2 cytokine productions as well as the serum levels of OVA-primed antigen-specific IgM and IgG 2a in vivo [ 27 ]. In the present study, we evaluated the immunomodulatory properties of ten Taiwanese Neolitsea plants on T helper cells.…”
Section: Discussionmentioning
confidence: 99%
“…Daibucarboline A, isolinderalactone, 7-omethylnaringenin, and prunetin isolated from the roots of N. daibuensis exhibited moderate inhibition of inducible nitric oxide synthase (iNOS) [ 40 ]. Hiiranlactone B and hiiranlactone D, isolated from the leaves of N. hiiranensis were classified as sesquiterpenes and possessed anti-inflammatory and immunomodulatory effects [ 27 , 34 ]. Thaliporphine, the alkaloid of the bark extracts of N. konishii , demonstrated vasoconstricting effects by promoting Ca 2+ entry [ 25 ] and possessed antioxidant, anti-inflammatory, and antiapoptotic activity to prevent cardiovascular system disorder in guinea pigs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human monocyte THP-1 cells were cultured in RPMI 1640 cell culture medium supplemented with 10% heat-inactivated fetal bovine serum (Hyclone) and 1% penicillin/streptomycin (Gibco) at 37 °C in 5% CO 2 . THP-1 cells (5 × 10 5 cells/well) were treated with different samples in 48-well plates in the presence of lipopolysaccharide (0.5 μg/mL) for 48 h. The supernatants were collected and quantified for TNF-alpha, as an indicator of cell proinflammatory responses, by standard sandwich enzyme-linked immunosorbent assay (ELISA) as previously described [ 21 , 22 ]. The TNF-alpha level in LPS group was designated as 100%, and the levels of TNF-alpha in each group was calculated according to the following formula: where a value over 100% indicates induction and a value smaller than 100% indicates inhibition.…”
Section: Methodsmentioning
confidence: 99%